PEMANFAATAN MINYAK CENGKEH PADA EDIBEL FILM TALAS SEBAGAI ANTIMIKROBA - Ismail Sulaiman; Rasdiansyah Rasdiansyah; Nelly Jessica Sihaloho (Department of Agroindustrial Technology, Bogor Agricultural University, 2023)
Edible film is one of the coating materials used to wrap food ingredients. The edible film can be used to preserve food products, especially ready-to-eat foods. The process of making the edible film was carried out in this study with the addition of clove oil, with the hope that it can become an antimicrobial on the edible film. The addition of clove oil to edible film applied to wet cakes aims to determine the effect of clove essential oil as an antimicrobial on edible film from taro starch base material. This study used a non-factorial Completely Randomised Design (CRD) with the effect of essential oil concentration. Starch and glycerol were used in the same concentration. The concentrations of clove oil used were 0% v/v, 0.5% v/v, 1% v/v and 1.5% v/v. The parameters used in this study were thickness, Water Vapor Permeability (WVP), water absorption, Scanning Electron Microcopies (SEM), Total Plate Count (TPC) test and water content. The results of this study showed that the concentration of clove oil had no effect on the thickness and value of Water Vapor Permeability (WVP) but affected the level of water absorption in edible film. The best edible film selected was the edible film added 0.5% essential oil with a thickness of 0.030 mm, WVP of 2.874 x10-11 kg.m/Pa.s.m2 and water absorption of 65.08% w/w. The edible film was selected based on the smallest layer so that it can be applied to layer cakes, in the best experiment it was stored for 4 days and then analysed for moisture content and TPC. The ability of edible film with 0.5% clove oil concentration can inhibit bacterial growth and maintain product quality for four days. Keywords: antimicrobial, edible film, clove oil, taro starch